Comparison of linear and angular measurement accuracy between cone beam computed tomography images and panoramic radiography - Mehrdad Abdinian; Reyhaneh Faghihian; Mehrnaz Safi (Wolters Kluwer Medknow Publications, 2017)
Purpose: Utilization of cone beam computed tomography (CBCT) in different fields of dentistry is on the rise; on the other hand, panoramic radiology as a screening technique is extensively used in dental procedures. Therefore, the objective of this study was to compare the accuracy of linear (horizontal-vertical) and angular measurements in CBCT images and panoramic radiographs. Materials and Methods: In this in vitro study, either mesiodistal width and the height, as well as angular measurement in anterior, canine, premolar and molar of the mandible and maxilla were measured. Each area was outlined by gutta-percha as opaque markers. The first and the second observers measured the linear and angular measurements twice with 2 weeks interval. Digital caliper, with the accuracy of 0.01 mm was used. A baseplate for reconstruction of the temporomandibular joint and a polyvinyl plastic pipe to reconstruct the spine were utilized. After the standard panoramic and CBCT radiography were obtained, observers used system-measuring menu to measure the distances between markers from the images. Based on sample size, all the above steps were repeated 10 times. Statistical analysis included an evaluation of the agreement between observers and the frequency of testing for each observer based on coefficient of concordance, as well as using paired t-test for comparing physical and radiographic quantities of different dimensions. P < 0.05 was established as a level of significant. Results: Comparison of the panoramic radiography with the CBCT in the anterior, canine, and molar of the maxilla and mandible showed a significant difference between two methods (P < 0.05). angular measurement in the premolar region of the maxilla and vertical measurement in the mandibular molar region also showed a significant difference between two methods (P > 0.05). The accuracy of panoramic radiography in comparison with CBCT in eighty samples regardless of the jaw and the area is approximately the same in angular measurement (P > 0.05). In contrast, in both horizontal and vertical positions, CBCT shows more meaningful result than panoramic radiography (P > 0.05). Conclusion: Comparison of CBCT and panoramic imaging revealed that CBCT in all three dimensions is more accurate than panoramic. The difference between these two techniques is maximized in the horizontal measurement and minimized in the angular measurement.